The effect of vascular risk factors on the efficacy of endolymphatic sac decompression surgery for Meniere’s disease: a retrospective cohort study - Li, Yiling; Gong, Fengyuan; Guo, Yangyang; Xu, Xianrong; Wang, Cuicui; Jin, Zhanguo (Frontiers in Neurology, 2023)
Objectives This study aimed to investigate the effect of vascular risk factors on the outcomes of endolymphatic sac decompression (ESD) surgery in patients with Meniere’s disease. Methods The study included 56 patients with Meniere’s disease, who had undergone unilateral ESD surgery. The patients’ vascular risk factors were assessed based on the preoperative 10-year atherosclerotic cardiovascular diseases risk classification. Those with no or low risk were defined as the low-risk group, while those with medium, high, or very high risk were defined as the high-risk group. The correlation between the vascular risk factors and ESD efficacy was evaluated by the comparison of vertigo control grade between the two groups. The functional disability score was also assessed to investigate whether ESD improved the quality of life in Meniere’s disease patients with vascular risk factors. Results After ESD, 78.95 and 81.08% of patients from the low-risk and high-risk groups, respectively, demonstrated at least grade B vertigo control; no statistically significant difference was observed (p = 0.96). The postoperative functional disability scores in both groups were significantly lower compared with those before surgery (p < 0.01), with a median decrease of two (1, 2) points in both groups. No statistically significant difference between the two groups was observed (p = 0.65). Conclusion Vascular risk factors have little effect on the efficacy of ESD in patients with Meniere’s disease. Patients with one or more vascular risk factors can still experience a not poor vertigo control and improved quality of life after ESD.